Students’Perceptions on Program Learning Outcomes: A Secondary Data Analysis of An Exit Survey - Nik Mohd Yusoff, Nik Nadhilah (Indonesian Journal of Education Methods Development, 2019)
Outcome based education (OBE) emphasized on designing, constructing, delivering and documenting the teaching and learning to be in line with the established program learning outcomes (PLO) by the Malaysian Qualification Framework (MQF) to improve the quality of learning. The study focuses on students’ perceptions on the PLO at the School of Quantitative Sciences (SQS), Universiti Utara Malaysia.A secondary data from an exit survey among graduating students of SQS has been analysed for this purpose. Study finding shows that on average, all respondents perceived that they werefairly strongly to strongly for all PLOs. The information obtained from the exit survey data is able to rank the PLO by its corresponding mean value in decreasing order.The purpose of this study is to obtain information on the extent to which the students have mastered the skills (PLO) from their own view.This study has been done by secondary data collection. The secondary data was from a 2017 Exit Survey with 46 respondents among graduating students of SQS, UUM. All of these students were enrolled in Bachelor of Science with Honors (Business Mathematics) program.All respondents perceived that they were at fairly strong to strong level for all PLO. The information obtained from the exit survey data is able to rank the PLO by its corresponding mean value in decreasing order.This study will be beneficial to curriculum providers as a reference for improvement by understanding the needs and current states of the students. Moreover, this research will provide recommendations on how to evaluate program learning outcomes.